The Transcription Factor C/EBPβ Promotes HFL-1 Cell Migration, Proliferation, and Inflammation by Activating lncRNA HAS2-AS1 in Hypoxia - Yang, Xue; Qi, Fei; Wei, Shanchen; Lin, Lianjun; Liu, Xinmin (Frontiers in Cell and Developmental Biology, 2021)
Objective Recent studies were widely concerned about the role of lncRNAs in hypoxic pulmonary hypertension (HPH). HAS2 was found significantly highly expressed in HPH, but the antisense of HAS2 (HAS2-AS1) has not been explored in HPH, providing a new potential therapeutic target of HPH. Methods In this study, human fetal lung fibroblast-1 (HFL-1) cells were cultured under hypoxia conditions to stimulate the pathological process of HPH. Transwell and wound-healing assays were used to detect HFL-1 cell migration, and CCK 8 assay was used to detect cell proliferation. The upstream transcription factor of HAS2-AS1 was predicted by JASPAR website, and the binding site between C/EBPβ and HAS2-AS1 was predicted by JASPAR, too. In order to verify the association between C/EBPβ and the HAS2 promoter region, we used chromatin immunoprecipitation (ChIP) and dual luciferase reporter gene detection, western blot to detect the expression of inflammation-related proteins, and qRT-PCR to detect the expression of HAS2-AS1 and HAS2. Idiopathic pulmonary fibrosis (IPF) with HPH patient microarray data was downloaded from the GEO database and analyzed by R software. Results Our study showed that HAS2-AS1 and C/EBPβ were highly expressed in hypoxic HFL-1 cells, and the knockdown of HAS2-AS1 expression could inhibit the proliferation, migration, and inflammatory response of HFL-1 cells. C/EBPβ binds to the promoter region of HAS2-AS1 and has a positive regulation effect on the transcription of HAS2-AS1. Furthermore, C/EBPβ can regulate the proliferation, migration, and inflammatory response of HFL-1 cells through HAS2-AS1. Conclusion This study suggested that C/EBPβ could upregulate HAS2-AS1 expression and induce HFL-1 cell proliferation, migration, and inflammation response.